1996
DOI: 10.1037/0022-3514.71.5.937
|View full text |Cite
|
Sign up to set email alerts
|

How are social support effects mediated? A test with parental support and adolescent substance use.

Abstract: This research tested how the effect of parental emotional and instrumental support on substance (tobacco, alcohol, and marijuana) use in adolescents is mediated. Data were from a sample of 1,702 adolescents surveyed between the 7th and 9th grades. Parental support was inversely related to substance use, and stress-buffering interactions were found at all assessment points. Structural modeling analyses indicated the effect of support was mediated through more behavioral coping and academic competence and less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
205
2
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(225 citation statements)
references
References 63 publications
(96 reference statements)
15
205
2
3
Order By: Relevance
“…In recent years, a number of studies have highlighted the importance of relational support for adolescents' psychosocial functioning. As a matter of fact, family and social support has been found to be inversely related to behavioural problems such as substance use (Wills & Clearly, 1996), delinquency (Windle, 1992), emotional problems, and low selfesteem levels.…”
Section: E Scabinimentioning
confidence: 99%
“…In recent years, a number of studies have highlighted the importance of relational support for adolescents' psychosocial functioning. As a matter of fact, family and social support has been found to be inversely related to behavioural problems such as substance use (Wills & Clearly, 1996), delinquency (Windle, 1992), emotional problems, and low selfesteem levels.…”
Section: E Scabinimentioning
confidence: 99%
“…A separate body of research has shown that poor parent-child communication and poor parental support are frequently associated with greater substance use among youth (Anderson & Henry 1994;Selnow, 1987;Wills & Cleary 1996). For example, infrequent communication has been found to be associated with higher rates of alcohol and tobacco use (Cohen et al 1994).…”
Section: Parent-child Relationshipsmentioning
confidence: 99%
“…For example, Allen, Moore, Kupermine, and Bell (1998) found that secure attachment, assessed through a structured interview, predicted competence with peers, lower levels of internalizing behaviors, and lower levels of deviant behavior. Parental support appears to influence health risk behavior through a variety of pathways, including adaptive coping, academic competence, and fewer deviant peer affiliations (Wills & Cleary, 1996). In addition, relations with parents may interact with other interpersonal factors to influence behavior (e.g., peer orientation, Bogenschneider, Wu, Raffaelli, & Tsay, 1998;Gerrard, Gibbons, Zhao, Russell, & ReisBergan, 1999).…”
Section: Etiology and Models Of Adolescent Health Behaviormentioning
confidence: 99%